A Review on Pharmacokinetics, Mechanism of Action and Side Effects of Probiotics - Farooq, Sumama (International Journal of Molecular Microbiology, 2023)
Maintaining a healthy balance in the gut flora is essential for a strong immune system. Gut bacteria play a role in regulating the immune system and preventing harmful germs from entering the bloodstream. Controlled experiments have reported that probiotic bacteria are microorganisms that provide health benefits when consumed and offer therapeutic benefits in treating various gastrointestinal disorders, including infectious diarrhea in children, recurrent Clostridium difficile-induced colitis, and specific inflammatory bowel diseases. This makes probiotic bacteria a promising therapeutic approach for alleviating human illnesses. While the precise mechanisms governing the communication between microorganisms and the host remain to be fully elucidated, a growing body of evidence suggests that gut bacteria can influence the functioning of the immune system at both a systemic and mucosal level. Recent and noteworthy discoveries indicate that manipulating the microbiota, the collective term for the trillions of microorganisms that live in the gut can exert an influence on the host, revealing novel pathways through which probiotics exhibit their beneficial effects. Additionally, the report delves into the potential adverse effects associated with probiotics, particularly in individuals with compromised immune systems, including instances of fungemia and bacteremia.